2018
DOI: 10.3390/cancers10110401
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Comparison of Proton Radiation Therapy, Volumetric Modulated Arc Therapy, and Three-Dimensional Conformal Radiotherapy Based on Intracranial Tumor Location

Abstract: (1) Background: Selecting patients that will benefit the most from proton radiotherapy (PRT) is of major importance. This study sought to assess dose reductions to numerous organs-at-risk (OARs) with PRT, as compared to three-dimensional conformal radiotherapy (3DCRT) and volumetric-modulated arc therapy (VMAT), as a function of tumor location. (2) Materials/Methods: Patients with intracranial neoplasms (all treated with PRT) were stratified into five location-based groups (frontal, suprasellar, temporal, pari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 45 publications
(47 reference statements)
1
25
0
2
Order By: Relevance
“…Radiation therapy implies external beam radiation therapy using photons or protons [37] (Table 1). In most cases, radiation therapy is administered at the time of progression after prior surgery.…”
Section: Radiation Therapymentioning
confidence: 99%
“…Radiation therapy implies external beam radiation therapy using photons or protons [37] (Table 1). In most cases, radiation therapy is administered at the time of progression after prior surgery.…”
Section: Radiation Therapymentioning
confidence: 99%
“…IMRT can be used to achieve excellent treatment outcomes for CC as well as to effectively reduce side effects such as radioactive cystitis and enteritis (5). Volumetric modulated arc therapy (VMAT) is an advanced form of IMRT; VMAT results in greater conformity and shorter treatment delivery time compared with IMRT (6). At our institution, definitive VMAT has been used since 2012 for treating patients with CC.…”
Section: Introductionmentioning
confidence: 99%
“…28 In comparative studies of radiation dosage to "organs at risk," which include the hippocampi, cochlea, optical structures, and thalami, particle radiation therapy plans actually resulted in an overall dosing reduction in all locations as compared to plans for 3D conformal radiotherapy and intensity-modulated radiotherapy. 1,2,20 Furthermore, pediatric patients receiving conventional photon-based radiation to fields encompassing cerebral vasculature demonstrated a significant risk of vasculopathy, with nearly 20% of subjects experiencing either a transient ischemic attack or an infarction within 13 years following therapy. 50 In the present review, the high-risk meningioma studies reported that the most common toxicity was radiation necrosis but at a rate lower than the radiation necrosis rates cited for photon-treated high-grade meningiomas, which range from 6.6% to 23%.…”
Section: Discussion Adverse Events Following Particle Therapymentioning
confidence: 99%